Impact of Reclamation Development on Sedimentation and Current Pattern in East Coast Surabaya (Pamurbaya) - Suntoyo Suntoyo; Hasan Ikhwani; Mohammad Iqbal Hidayah (International Journal of Offshore and Coastal Engineering, 2017)
Reclamation is an effort to establish a new land area either in coastal areas or in the middle of the ocean. In Pamurbaya area a number of property projects both housing and apartments is still continuing. Environmental impacts of the coastal reclamation project is in the potential increase of flooding. The changes include the extent of the cluster, the composition of river sediments, the tidal pattern, the pattern of ocean currents along the coast and damaging the water system. This study examines changes in current patterns, morphology, and sedimentation rate due to the reclamation modeled using Delft3D software. The pattern of current flow after the reclamation has changed. Basic surface changes that occur before and after reclamation in each crossection is by difference, crossection 1 = +0.22 m, crossection 2 = -0.19 m, and crossection 3 = +0.11 m. The sign (+) shows the occurrence of sedimentation, while (-) is erosion. The condition after the reclamation in crossection 1 is sedimentation, crossection 2 is erosion, and crossection 3 is sedimentation. The difference in intensity is very small, therefore the erosion and sedimentation which took place after reclamation is not too significant.